2020
DOI: 10.1007/s00436-020-06973-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors associated with Leishmania infantum in dogs in Sardinia (Italy), an endemic island for leishmaniasis

Abstract: Leishmaniasis is a widespread, vector-borne parasitosis causing clinical manifestations in animals and in humans. In dogs, Canine Leishmaniasis has been reported in as much as 50 countries and the Mediterranean basin is known to be one of the most affected zones. Within these areas, the Island of Sardinia (Italy) has long been considered endemic for leishmaniasis and the presence of two arthropod vectors has recently been reported there. Nevertheless, to date, no epidemiological surveys regarding CanL have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 50 publications
(96 reference statements)
4
24
0
Order By: Relevance
“…A significant difference in prevalence was found between sexes, with males showing higher seroprevalence. Other authors reported a higher seroprevalence in males [ 34 , 36 ]. This result could be due to the roaming behaviour of male dogs in rural areas or the outdoor attitude of male guard dogs, as reported in a study carried out in the study area [ 21 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A significant difference in prevalence was found between sexes, with males showing higher seroprevalence. Other authors reported a higher seroprevalence in males [ 34 , 36 ]. This result could be due to the roaming behaviour of male dogs in rural areas or the outdoor attitude of male guard dogs, as reported in a study carried out in the study area [ 21 ].…”
Section: Discussionmentioning
confidence: 93%
“…seropositivity increased with the dog age [14,17,[32][33][34][35]. This evidence could be attributed to repeated exposure to Leishmania during the years.…”
Section: Plos Onementioning
confidence: 89%
See 1 more Smart Citation
“…However, transmission in the absence of the vector has been reported, including infection due to blood transfusion [ 4 , 5 ], vertical transmission in the absence of known suitable biological vectors [ 6 8 ], and venereal transmission from the semen of naturally infected males to susceptible bitches [ 9 , 10 ]. The incubation period after sand fly infection can extend from 3 months to 7 years [ 11 ], and clinical cases of leishmaniosis of pups younger than 5 months of age are extremely rare [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant difference in prevalence was found between sexes, with males showing higher seroprevalence. Other authors reported a higher seroprevalence in males [34,36]. This result could be due to the roaming behaviour of male dogs in rural areas or the outdoor attitude of male guard dogs, as reported in a study carried out in the study area [21].…”
Section: Plos Onementioning
confidence: 53%